2019
DOI: 10.1002/ecs2.2611
|View full text |Cite
|
Sign up to set email alerts
|

Wolverines in winter: indirect habitat loss and functional responses to backcountry recreation

Abstract: Outdoor recreation is increasingly recognized to impact nature and wildlife, yet few studies have examined recreation within large natural landscapes that are critical habitat to some of our most rare and potentially disturbance‐sensitive species. Over six winters (2010–2015) and four study areas (>1.1 million ha) in Idaho, Wyoming, and Montana, we studied the responses of wolverines (Gulo gulo) to backcountry winter recreation. We fit Global Positioning System (GPS) collars to 24 individual wolverines and acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 89 publications
2
69
0
Order By: Relevance
“…For example, moose preferentially selected habitats away from areas of high snowmobile-trail density (Colescott andGillingham 1998, Harris et al 2014) and intensive snowmobile activity displaced woodland caribou (R. tarandus caribou) from suitable habitat (Seip et al 2007). Female wolverines tend to avoid motorized winter recreation resulting in significant habitat loss (Heinemeyer et al 2019). Results from our study demonstrated that lynx were most responsive to environmental heterogeneity related to habitat characteristics as hypothesized ( Table 2, Fig.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…For example, moose preferentially selected habitats away from areas of high snowmobile-trail density (Colescott andGillingham 1998, Harris et al 2014) and intensive snowmobile activity displaced woodland caribou (R. tarandus caribou) from suitable habitat (Seip et al 2007). Female wolverines tend to avoid motorized winter recreation resulting in significant habitat loss (Heinemeyer et al 2019). Results from our study demonstrated that lynx were most responsive to environmental heterogeneity related to habitat characteristics as hypothesized ( Table 2, Fig.…”
Section: Discussionsupporting
confidence: 53%
“…), and wolverines ( Gulo gulo , Heinemeyer et al. ). We believe the patterns of spatial separation we documented between Canada lynx and winter recreationists, such as in areas of low tree canopy cover selected by snowmobilers, were mostly a function of resource‐use decisions rather than a landscape of fear that precluded access.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations